Complex phenotype of hypercholesterolaemia in a family with both ABCG8 and APOB mutations - Padeira, G. (2017)
Familial Hypercholesterolemia (FH) is the most common of all genetic hypercholesterolaemias with defects in LDLR, APOB and PCSK9 accounting for the majority of cases. However, there are other rare disorders like sitosterolaemia that can present the same phenotype. Both can cause premature atherosclerosis but have distinctive dietetic and therapeutic intervention.